EFEKTIVITAS KOMUNIKASI DAKWAH: KECERDASAN KOMUNIKASI DAN RETORIKA DAKWAH - Suharto Suharto (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2014)
The effectiveness of communication in doing da’wah is demanded for the development of da’wah in this era of global competition. Therefore, the presence of various models of communication today makes communication both as secondary and primary tool. Moslem preachers can build a design of da’wah communication based on technology to make it effective. In improving the effectiveness of da’wah communication, intellectual capability and da’wah rethoric are required including the use of communication technology. Implicitly, communication technology has become a main prerequisite for Moslem preachers to modernize da’wah rethoric in preaching. However, it is communication capabilities which make da’wah rethoric being carried out well, and in turn, da’wah rethoric will have a high value in the community.